Manufacturing Firm Size Distribution in Iran Evidence from Food & Beverages and Non-Metallic Mineral Products - Mohammad Ali Feizpour; Marjan Habibi (International Journal of Business and Development Studies, 2014)
Empirical studies have shown that the size distribution of firms can be described as a lognormal or Pareto distribution. However, these studies have focused on developed countries and little attention has been devoted to developing countries. Using the variable of number of employees as a measure of firm size, this paper investigates the shape of firm size distribution in the food & beverages industry and also in the non-metallic mineral products industry over the period of 1997-2005. Our findings show that there is no universality of the size distribution of firms between industries. In other words, the size distribution varies in terms of kind of industry, so that our results make it clear that food & beverages industry follows lognormal distribution, conversely to other industry which a good representation of Pareto distribution. From policy point of view, knowledge about firm size distribution caused new entrance firms to decide wisely and therefore provide improvement on performance after entry.